THE LEADERSHIP STYLE MODEL THAT BUILDS WORK BEHAVIOR THROUGH ORGANIZATIONAL CULTURE - Arasy Alimudin; Agus Sukoco (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2017)
The changes in organizational culture and work behavior is an important process for companies to survive in competition. And a change of leadership that is part of the change will pose challenges and reactions to the interests of its human resources. The research approach used quantitative research and included explanatory research to explain the causal relationship among variables through hypothesis testing with partial least squares path modeling (PLS-SEM) analysis technique. The results showed the influence of leadership style on positive work behavior but not significant. Reward and punishment no significant effect on work behavior. The organizational culture had a positive and significant effect on work behavior. The leadership style had a positive and significant effect on organizational culture. The reward and punishment had positive and significant effect on organizational culture. The findings of this study showed that participative leadership style model using reward and punishment mechanism could improve work behavior and organizational culture.